Sweet Bakery Enterprise / Sarina Azmi... [et al.] - Azmi, Sarina; Dzakaria, Rosmaliza; Ismail, Jamilah; Ismail, Roslina; Mat Shah, Normalina (2001)
Sweet Bakery Enterprise was a partnership company that include of five members. This company was located at Alor Setar, Kedah and was started their business on 1 January 2002. Main activity of their company are by serve product and services for customer. In Sweet Bakery Cafe, they produce the product of food. Other than that they also provide a new recipe ideas of bun, ice-cream and drinks. They also take reserve such as wedding, birthday and many more.